2010
DOI: 10.1016/j.worlddev.2009.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Presence, Spillovers, and Productivity: Evidence from Ghana

Abstract: This paper investigates the effect of foreign presence on the productivity of manufacturing industries in Ghana, using firm level panel data. We examine both labor and total factor productivity (TFP), which we compute using the Levinsohn and Petrin (2003) methodology. We control for a number of observed factors as well as unobserved heterogeneity in several dimensions. We find robust evidence that the presence of foreign firms in a sector has a negative effect on domestically owned, but a positive effect on mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 33 publications
5
43
0
Order By: Relevance
“…This is expected since foreign firms will generally have a longer track record, and they stand in a better position than the local firms to get access to the domestic funds. This is supported by findings from Frimpong and Oteng-Abayie [2], Asiedu [3] and Waldkirch and Ofosu [4]. Thus, though FDI can generally be seen to promote growth, contrary to this view, these studies among others have found that FDIs are always not beneficial to host countries 1 .…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…This is expected since foreign firms will generally have a longer track record, and they stand in a better position than the local firms to get access to the domestic funds. This is supported by findings from Frimpong and Oteng-Abayie [2], Asiedu [3] and Waldkirch and Ofosu [4]. Thus, though FDI can generally be seen to promote growth, contrary to this view, these studies among others have found that FDIs are always not beneficial to host countries 1 .…”
Section: Introductionmentioning
confidence: 54%
“…Asiedu [3] also concludes that the effect of FDIs through spillovers in areas of production, technology transfers and job creation have still not been realised. Similarly, Waldkirch and Ofosu [4] find a negative effect of the presence of FDI on domestically-owned firms in Ghana.…”
Section: Review On Fdi Growth and Financial Developmentmentioning
confidence: 88%
“…Typically, developing countries offer a range of incentives such as income tax rebates, import duty exemptions and infrastructure subsidies to attract foreign direct investment (Aitken and Harrison, 1999;Waldkirch and Ofosu, 2010). In addition to the direct benefits of an additional source of capital, the flow of foreign direct investment (FDI) is expected to yield benefits such as enhanced employment opportunities, foreign exchange, and arguably, most importantly, the prospect of acquiring new technology and other intangible knowledge, which may spill over to the host country and allow domestic firms to improve their performance (see Ramirez, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Foreign subsidiaries also exhibit a strong tendency to remit profits by manipulating prices, and the type and quantity of their international transactions are mostly kept within the boundaries of the firm (Waldkirch and Ofosu, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation